The role of cognitive reserve and clinical symptoms in the association between genetic liability for educational attainment and functioning in first-episode psychosis: A mediation analysis - Derek Clougher; Àlex G. Segura; Maria F. Forte; Gisela Mezquida; Manuel J. Cuesta; Eduard Vieta; Silvia Amoretti; Antonio Lobo; Ana González-Pinto; Covadonga M. Díaz-Caneja; Alexandra Roldán; Giovanna Fico; et al. (European Psychiatry)
Abstract